Comparison of two methods for selecting minimum stimulation levels used in programming the nucleus 22 cochlear implant. - Skinner, Margaret W.; Holden, Laura K.; Holden, Timothy A. (Journal of Speech, Language & Hearing Research, 1999)
Minimum stimulation levels for active electrodes in a Nucleus 22 cochlear implant were set at threshold (clinical default value) and raised levels (M = +2.04 dB) to determine if raised levels would improve recipients' understanding of soft speech sounds with the SPEAK speech coding strategy. Eight postlinguistically deaf adults participated in a 4-phase A1B1A2B2, test design. Speech recognition was evaluated with consonant-vowel nucleus-consonant (CNC) words in quiet and sentences in noise, both presented at 50, 60, and 70 dB SPL during 2 weekly sessions at the end of each phase. Group mean scores were significantly higher with the raised level program for words and phonemes at 50 and 60 dB SPL and for sentences at 50 and 70 dB SPL. All participants chose to use the raised level program in everyday life at the end of the study. The results suggest that clinical use of a raised level program for Nucleus 22 recipients has the potential to make soft sounds louder and, therefore, more salient in everyday life. Further research is needed to determine if this approach is appropriate for other cochlear implant devices. Reprinted by permission of the publisher.